MAIN STAGES OF CONTINENTAL CRUST FORMATION IN THE WESTERN ALDAN SHIELD: CONSTRAINTS FROM SM-ND ISOTOPE SYSTEMATICS OF CENOZOIC SANDS IN THE CHARA AND TOKKA BASINS - A. B. Коtоv; T. M. Skovitina; V. P. Kovach; S. D. Velikoslavinsky; D. V. Lopatin; E. V. Sklyarov; E. V. Tolmacheva; O. V. Bobrovskaya (Геодинамика и тектонофизика, 2017)
Previous geochronological and Sm-Nd isotopegeochemical studies have identified the main stages of the Precambrian continental crust formation in the central and eastern parts of the Aldan Shield [Kotov et al., 2006], while its western part (Chara-Olekma Geoblock) has not been adequately investigated yet in this respect.